PENGUATAN REGULASI DAN INOVASI DALAM PENGEMBANGAN PASAR MODAL SYARIAH - Dea Risti Aulia; Baidhowi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Abstrak. The Islamic capital market has a strategic role in supporting economic growth based on sharia principles. This article discusses regulatory strengthening and innovation in the development of the Islamic capital market, including legal aspects, investment products, and challenges faced. Strong regulations are needed to ensure compliance with sharia principles and increase investor confidence. Innovation in Islamic financial products, such as Islamic stocks and sukuk, is key in attracting investors and expanding market access. Islamic capital markets also play a role in creating a sustainable and inclusive investment ecosystem, in line with Islamic principles of fairness and transparency. In addition, good cooperation between the government, market players, and academics is an important factor in encouraging the development of the Islamic capital market. With the support of technology and digitalization, Islamic financial products can be more easily accessed by the wider community, thereby increasing investor participation. With a comprehensive approach, strengthening regulations and innovation is expected to increase the competitiveness of the Islamic capital market and encourage sustainable economic growth. Keywords: Islamic Capital Market, Regulation, Innovation, Islamic Shares Abstrak. Pasar modal syariah memiliki peran strategis dalam mendukung pertumbuhan ekonomi berbasis prinsip syariah. Artikel ini membahas penguatan regulasi dan inovasi dalam pengembangan pasar modal syariah, termasuk aspek hukum, produk investasi, serta tantangan yang dihadapi. Regulasi yang kuat diperlukan untuk memastikan kepatuhan terhadap prinsip syariah dan meningkatkan kepercayaan investor. Inovasi dalam produk keuangan syariah, seperti saham syariah dan sukuk, menjadi kunci dalam menarik minat investor dan memperluas akses pasar. Pasar modal syariah juga berperan dalam menciptakan ekosistem investasi yang berkelanjutan dan inklusif, sejalan dengan prinsip keadilan dan transparansi dalam Islam. Selain itu, kerja sama yang baik antara pemerintah, pelaku pasar, dan akademisi menjadi faktor penting dalam mendorong perkembangan pasar modal syariah. Dengan dukungan teknologi dan digitalisasi, produk-produk keuangan syariah dapat lebih mudah diakses oleh masyarakat luas, sehingga meningkatkan partisipasi investor. Dengan pendekatan yang komprehensif, penguatan regulasi dan inovasi diharapkan dapat meningkatkan daya saing pasar modal syariah serta mendorong pertumbuhan ekonomi yang berkelanjutan. Kata Kunci: Pasar Modal Syariah, Regulasi, Inovasi, Saham Syariah.